Fairway to fractures: income inequality and violent crime as the driving factors for golf club related assaults - a case series of 21 compound skull fractures in South Africa. - Grobler, Ruan (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2024.